Doped hafnium oxide-based ferroelectric film based on doping distribution regulation and control and preparation method and application of doped hafnium oxide-based ferroelectric film
By adopting a doping distribution regulation preparation method in traditional doped hafnium oxide-based ferroelectric films, the film's shortcomings in insulation characteristics, ferroelectric properties and durability are solved, and the film has achieved higher residual polarization strength and better durability, which is suitable for the manufacturing of a variety of electronic devices.
Patent Information
- Application Number
- CN202411830372.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-14
AI Technical Summary
Traditional doped hafnium oxide-based ferroelectric films have shortcomings in insulation characteristics, ferroelectric properties and durability, resulting in poor reliability and consistency in practical applications.
Using a preparation method based on doping distribution regulation, a [(Hf0.5Zr0.5O2)y-Alx-(Hf0.5Zr0.5O2)y]z ferroelectric film with different doping concentrations was deposited by repeated use of ALD technology on the substrate, and the top electrode was plated after high-temperature annealing treatment to form a doped hafnium oxide-based ferroelectric film with excellent performance.
Higher residual polarization strength, better insulation characteristics and better durability are achieved, making the hafnium oxide-based ferroelectric thin film regulated by doping distribution suitable for the manufacturing of random access memory, ferroelectric field effect transistors and other devices.
Smart Images

Figure CN119615117A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field, and in particular relates to a doped hafnium oxide-based ferroelectric film based on doping distribution regulation and a preparation method and application thereof. Background Art
[0002] With the rapid development of information technology, especially in the fields of smart electronic devices and nanotechnology, ferroelectric materials have attracted widespread attention due to their unique electrical properties and excellent non-volatile storage characteristics. As a new type of ferroelectric material, doped hafnium oxide (HfO2) has great application potential in the next generation of non-volatile memory (such as FeRAM, Flash, etc.) and microelectronic devices due to its high remnant polarization, excellent thermal stability and adjustable electrical properties. Therefore, the development of doped hafnium oxide-based ferroelectric films with excellent performance has become an important research direction in the current field of materials science and engineering.
[0003] Although the traditional preparation method has improved the performance of doped hafnium oxide films to a certain extent, it still faces some bottlenecks. For example, the presence of uneven doping concentration and defects may lead to unstable dielectric and ferroelectric properties of the film, limiting its reliability and consistency in practical applications. In addition, the selection of doping elements and their distribution have an important influence on the crystal structure and electrical properties of the film. Reasonable doping distribution regulation is the key to achieving high-performance ferroelectric films.
[0004] Therefore, in order to control the performance of hafnium oxide-doped ferroelectric films, developing a new doping distribution control method to optimize the microstructure and macroscopic properties of the films has become a scientific and technological challenge that needs to be solved urgently. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a doped hafnium oxide-based ferroelectric film based on doping distribution regulation and its preparation method and application in view of the deficiencies in the above-mentioned prior art, so as to solve the technical problems of poor insulation characteristics, ferroelectric properties and durability of hafnium oxide-based ferroelectric films under traditional doping structures.
[0006] The present invention adopts the following technical solutions: A method for preparing a doped hafnium oxide-based ferroelectric thin film based on doping distribution regulation comprises the following steps: The unit structure of xyx is selected according to the doping concentration, and the ALD technology is repeatedly used on the substrate to obtain different doping concentrations [(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ]z A ferroelectric thin film, wherein x is the number of cycles of dopants in a unit structure, y is the total number of cycles of hafnium oxide and zirconium oxide in the unit structure, z is the number of repetitions of the unit structure, and the basic unit film has a doping concentration of y / 2x; =[(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z The ferroelectric film is plated with a top electrode and a bottom electrode, and then subjected to a high temperature annealing treatment to obtain a doped hafnium oxide-based ferroelectric film regulated based on doping distribution.
[0007] Preferably, the ALD technique is repeatedly used on the substrate to obtain different doping concentrations of [(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z Ferroelectric thin film Ferroelectric thin film specifically refers to: Plasma-enhanced atomic layer deposition technology is used to alternately deposit a set number of Hf layers on the substrate. 0.5 Zr 0.5 O2 film; Using plasma enhanced atomic layer deposition technology, Hf 0.5 Zr 0.5 A set number of Al2O3 films are deposited on the O2 film; Plasma enhanced atomic layer deposition technology was used to prepare Hf 0.5 Zr 0.5 O2 film deposition and Hf on substrate 0.5 Zr 0.5 O2 thin film with the same number of Hf 0.5 Zr 0.5 O2 film; Repeat the above steps several times until a [(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z Ferroelectric thin films.
[0008] Preferably, a set number of layers of Hf are alternately deposited on the substrate. 0.5 Zr 0.5O2 film is specifically: Using [(CH3)2N]4Hf(TDMAH) as Hf source, [(CH3)2N]4Zr(TDMAZ) as Zr source, and oxygen plasma as oxygen source, one cycle of ZrO2 and one cycle of HfO2 were alternately grown on a p-type Si substrate to obtain a set number of layers of Hf 0.5 Zr 0.5 O2 film.
[0009] Preferably, ZrO2 and HfO2 are alternately cycled 1 to 12 times and 1 to 12 times, respectively, keeping the number of cycles of ZrO2 the same as the number of cycles of HfO2.
[0010] Preferably, the dopant is any one of SiO2, Al2O3, La2O3, Gd2O3, and Y2O3.
[0011] Preferably, in Hf 0.5 Zr 0.5 The specific method of depositing a set number of Al2O3 films on an O2 film is: Plasma enhanced atomic layer deposition technology was used, with (CH3)3Al(TMA) as Al source and oxygen plasma as oxygen source. 0.5 Zr 0.5 A certain number of Al2O3 films are grown on the O2 film to complete the Hf 0.5 Zr 0.5 Al doping of O2 thin films; Using [(CH3)2N]4Hf(TDMAH) as Hf source, [(CH3)2N]4Zr(TDMAZ) as Zr source, and oxygen plasma as oxygen source, one cycle of ZrO2 and one cycle of HfO2 were alternately grown on Al2O3 film to obtain the same number of layers of Hf as in the substrate. 0.5 Zr 0.5 O2 thin film, obtain yxy (Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y Basic unit.
[0012] Preferably, the obtained [(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z The top electrode and bottom electrode of the ferroelectric thin film sample are specifically: Using the electrode material as the target, an ion sputtering coating process is used to grow a bottom electrode and a dot top electrode with a diameter of 50~700μm, and the electrode thickness is 20~120nm.
[0013] Preferably, the high temperature annealing is specifically: The sample obtained from S2 was subjected to high temperature annealing at 600-800°C for 10-600s at a heating rate of 50°C / s under standard atmospheric pressure. The annealing atmosphere was any one of vacuum, nitrogen, and nitrogen-hydrogen mixed gas.
[0014] Another technical solution of the present invention is to provide a hafnium oxide-doped ferroelectric film based on doping distribution regulation.
[0015] Another technical solution of the present invention is the application of doped hafnium oxide-based ferroelectric thin films based on doping distribution regulation in random access memory, ferroelectric field effect transistors, ferroelectric memristors, and ferroelectric enhanced photodetectors.
[0016] Compared with the prior art, the present invention has at least the following beneficial effects: A method for preparing doped hafnium oxide-based ferroelectric thin films based on doping distribution regulation has higher residual polarization strength, better insulation properties, no significant wake-up effect, and better durability without the need for additional processes. It can be widely used in the manufacture of random access memory, ferroelectric field effect transistors, ferroelectric memristors, ferroelectric tunnel junctions, ferroelectric enhanced photodetectors, and other devices; the Hf obtained by regulating the doping distribution 0.5 Zr 0.5 Compared with the uniformly doped hafnium oxide film, the Al-doped layer has a stronger effect on the Hf 0.5 Zr 0.5 The stress generated by the clamping and induced lattice distortion of O2 is more uniform. Under the influence of this uniform Al layer, the Hf 0.5 Zr 0.5 The O2 film exhibits a higher remnant polarization strength. At the same time, the uniform distribution of oxygen vacancies and other defects also makes the film more durable.
[0017] Furthermore, different doping concentrations are set according to the actual required process conditions such as annealing temperature, film thickness, etc., so that the film is suitable for different processes and usage requirements.
[0018] Furthermore, hafnium oxide and zirconium oxide are alternately deposited in cycles by atomic layer deposition, so that the ratio of hafnium oxide to zirconium oxide is always maintained at 1:1, thereby forming Hf 0.5 Zr 0.5 O2 film.
[0019] Further, by alternately cycling 1 to 12 times of hafnium oxide and 1 to 12 times of zirconium oxide, keeping the number of cycles 1:1, and the total number of cycles being y, the desired corresponding (Hf 0.5 Zr 0.5 O2) y film.
[0020] Furthermore, the dopant is one of SiO2, Al2O3, La2O3, Gd2O3, and Y2O3, which can effectively change the lattice stress in the film, thereby increasing the Hf 0.5 Zr 0.5 Ferroelectricity of O2 thin films.
[0021] Furthermore, by 0.5 Zr 0.5 O2) y A required number of aluminum oxide thin films are deposited to obtain an aluminum-doped hafnium oxide-based ferroelectric thin film with a specific doping concentration.
[0022] Furthermore, an electrode is plated on the doped hafnium oxide-based ferroelectric film to form a structure required for easily generating a ferroelectric phase during rapid annealing.
[0023] Furthermore, through rapid annealing at a specific temperature, the doped hafnium oxide film is transformed from amorphous to crystalline, forming a crystal phase with ferroelectric properties, thereby making the film have excellent ferroelectric properties.
[0024] This application proposes a hafnium oxide-based ferroelectric film based on doping structure regulation, which achieves higher residual polarization intensity than uniformly doped samples without additional process conditions; this innovation enables the devices prepared at the same cost to have better performance. In addition, the samples with doping structure regulation show higher durability, and the prepared devices are more durable and reliable than similar products.
[0025] In summary, the present invention significantly improves the performance of annealed ferroelectric films under electrode-free constraints, provides an in-depth understanding of the ferroelectric principle of HfO2 films, and promotes the development of the field of new practical ferroelectric films.
[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings to be used in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 A flow chart of preparing a hafnium oxide-based ferroelectric thin film based on doping distribution regulation provided by the present invention; Figure 2 The hysteresis loop diagram of the hafnium oxide-based ferroelectric thin film of Examples 1 to 3 provided by the present invention; Figure 3 The hysteresis loop diagram of the hafnium oxide-based ferroelectric thin film of Examples 4 to 6 provided by the present invention; Figure 4 1 is a hysteresis loop diagram of the hafnium oxide-based ferroelectric thin film of Comparative Examples 1 and 2 provided by the present invention; Figure 5 is a hysteresis loop diagram of the hafnium oxide-based ferroelectric thin film of Comparative Example 3 provided by the present invention; Figure 6 is a wake-up characteristic diagram of the hafnium oxide-based ferroelectric thin film of Example 3 and Comparative Examples 2 and 3 provided by the present invention; Figure 7 The present invention provides the breakdown characteristics of Example 3 and Comparative Examples 2 and 3; Figure 8 is a fatigue cycle characteristic diagram of the hafnium oxide-based ferroelectric thin film of Example 3 and Comparative Examples 2 and 3 provided by the present invention; Fig. 9 The present invention provides a comparison diagram of leakage current characteristics before and after fatigue in Example 3; Fig.10 is a comparison diagram of leakage current characteristics before and after fatigue of comparative example 2 provided by the present invention; Fig.11 It is a comparison diagram of the leakage current characteristics before and after fatigue of comparative example 3 provided by the present invention. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0031] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0032] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.
[0033] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.
[0034] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6-22" represents that all real numbers between "6-22" are listed in this document, and "6-22" is just an abbreviation of these numerical combinations.
[0035] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.
[0036] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0037] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.
[0038] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.
[0039] The present invention provides a doped hafnium oxide-based ferroelectric film based on doping distribution control, and its preparation method and application, which can significantly improve its insulation performance, ferroelectric performance and durability by precisely controlling the distribution of doping elements, thus meeting the needs of future high-performance electronic devices. Such technological innovation will open up new directions for the application of ferroelectric materials and promote further development in related fields.
[0040] The present invention provides a method for preparing a doped hafnium oxide-based ferroelectric thin film based on doping distribution regulation, comprising the following steps: S1, substrate pretreatment; S101, using alcohol and high-purity water to clean the heavily doped substrate respectively; The substrate is any one of silicon dioxide / silicon, silicon, germanium, sapphire, mica or gold foil.
[0041] S102, ultrasonically cleaning the pre-cleaned substrate, etching the substrate with an HF solution to remove the SiO2 oxide layer on the surface of the silicon wafer, and setting the cleaning time to 5 minutes; S103, clean the substrate again using alcohol and high-purity water respectively.
[0042] S2, using ALD technology on the substrate obtained in step S1, selecting xyx according to the required doping concentration, repeating the above unit multiple times to obtain [(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z Ferroelectric thin film, wherein x is the number of cycles of dopants, y is the total number of cycles of hafnium oxide and zirconium oxide, z is the number of repetitions of the unit structure, and the doping concentration is x / 2y; S201, using plasma enhanced atomic layer deposition technology, alternately deposit a certain number of Hf layers on the substrate 0.5 Zr 0.5 O2 film; Plasma-enhanced atomic layer deposition (PEALD) was used to grow 8 to 24 layers of HfO2 on the substrate alternately, using [(CH3)2N]4Hf(TDMAH) as the Hf source, [(CH3)2N]4Zr(TDMAZ) as the Zr source, and oxygen plasma as the oxygen source. 0.5 Zr 0.5 O2 film.
[0043] Alternately cycle either ZrO2 1 to 15 times and HfO2 1 to 15 times, keeping the number of cycles of ZrO2 consistent with the number of cycles of HfO2.
[0044] The dopant is any one of SiO2, Al2O3, La2O3, Gd2O3, and Y2O3.
[0045] S202, using plasma enhanced atomic layer deposition technology, Hf 0.5 Zr 0.5 1~2 layers of Al2O3 film are deposited on the O2 film; Plasma enhanced atomic layer deposition technology was used, with (CH3)3Al(TMA) as Al source and oxygen plasma as oxygen source. 0.5 Zr 0.5 1~2 layers of Al2O3 thin film are grown on the O2 thin film to complete the Hf 0.5 Zr 0.5 Al doping of O2 thin films.
[0046] Plasma enhanced atomic layer deposition technology was used, with [(CH3)2N]4Hf(TDMAH) as the Hf source, [(CH3)2N]4Zr(TDMAZ) as the Zr source, oxygen plasma as the oxygen source, and the growth temperature was 220-280°C. One cycle of ZrO2 and one cycle of HfO2 were alternately grown on the Al2O3 film to obtain the same number of layers of HfO2 as in step S201. 0.5 Zr 0.5 O2 film.
[0047] S203, using plasma enhanced atomic layer deposition technology, depositing the same number of layers Hf as in step S201 on the thin film prepared in step S202 0.5 Zr 0.5 O2 film; S204, repeating steps S201, S202, and S203 for multiple times until a [(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z Ferroelectric thin films.
[0048] S3, plating a top electrode and a bottom electrode for the sample obtained in step S2.
[0049] The electrode material is used as a target material, and an ion sputtering coating process is adopted to grow the bottom electrode and a dot top electrode with a diameter of 50-700 μm. The thickness of the top electrode and the bottom electrode is 20-120 nm.
[0050] The electrode material is any one of common metal materials (such as Pt, Au), carbon-based materials (such as graphite, carbon nanotubes, etc.), alloy materials (such as Ni-Cr alloy, titanium alloy, etc.), and coating materials (such as platinum-plating, ITO, TiN).
[0051] S4. Perform high temperature annealing on the sample obtained in step S3.
[0052] The sample obtained from S2 was subjected to high temperature annealing at 600-800°C for 10-600s at a heating rate of 50K / s under standard atmospheric pressure.
[0053] The annealing atmosphere is any one of vacuum, nitrogen, and nitrogen-hydrogen mixed gas.
[0054] A hafnium oxide-doped ferroelectric film based on doping distribution regulation is prepared by the above method. The Al-doped Hf 0.5 Zr 0.5O2 (HZO) thin film materials have ferroelectric properties. Compared with the prior art, the present invention adopts plasma enhanced atomic layer deposition process to overlap and grow HZO ferroelectric films and Al-doped films of different thicknesses and numbers of layers on a p-type Si substrate. The process is simple and controllable. On the one hand, the Al-doped layer produces a clamping effect similar to that of an electrode, which promotes the formation of a ferroelectric orthorhombic phase of the HZO ferroelectric film during rapid annealing. Moreover, compared with uniformly doped samples, the stress clamping effect of the Al-doped layer on hafnium oxide in the sample with the doping structure regulated is more uniform, which is more conducive to inducing the growth of ferroelectric phases. On the other hand, the relatively small Al 3+ Replacement of Hf 4+ The HfO2 unit cell has lattice distortion, which also promotes the formation of ferroelectric orthorhombic phase. The sample after doping structure adjustment also makes the lattice distortion more uniform, which promotes the growth of ferroelectric phase. Under the action of these two kinds of Al doping, the ferroelectricity of HZO film is not only improved, but also the coercive field is greatly reduced, which improves the durability of HZO ferroelectric film, making the HZO film after doping distribution adjustment have higher residual polarization strength and durability.
[0055] The invention discloses a hafnium oxide-doped ferroelectric film regulated by doping distribution, which can be applied to electronic devices such as random access memory, ferroelectric field effect transistor, ferroelectric memristor, ferroelectric enhanced photoelectric detection and the like. Compared with a uniformly doped hafnium oxide-based film, the HZO film regulated by doping distribution obtained by adopting the above technical scheme has a more uniform clamping effect of the doped Al layer on HZO and a more uniform stress effect of inducing lattice distortion. Under the action of the uniform Al layer, the HZO film regulated by doping distribution exhibits a higher residual polarization intensity, and due to the uniform distribution of defects such as oxygen vacancies, the HZO film regulated by doping distribution exhibits a higher durability.
[0056] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0057] Hafnium oxide-based ferroelectric thin films have become a hot topic in the field of microelectronics due to their excellent material properties. Their main advantages include high dielectric constant, good ferroelectricity, excellent thermal stability, low power consumption, and good compatibility with existing CMOS processes. Through structural regulation, hafnium oxide thin films can achieve greater remnant polarization and better durability, which provides significant advantages for their performance in high-performance applications.
[0058] Specifically, doping distribution regulation can improve its ferroelectric properties, thereby enhancing the residual polarization intensity, which means that after the electric field is applied, the film can more effectively retain the charge state and ensure the reliability of data storage. In addition, improving durability will extend the service life of the device, reduce the probability of performance degradation of the device during repeated operations, and ensure stable operation under harsh conditions. The comprehensive performance improvement brought about by this structural regulation makes hafnium oxide films more suitable for widespread use in non-volatile memories, sensors, and next-generation logic circuits, meeting the needs of modern electronic devices for high efficiency and high reliability. Therefore, the present application proposes a hafnium oxide-based ferroelectric film without electrode constraint annealing and a preparation method thereof.
[0059] First, the substrate is cleaned.
[0060] Specifically, in the first step, alcohol and high-purity water are used to clean the heavily doped p-type Si substrate respectively; In the second step, the pre-cleaned p-type Si substrate is ultrasonically cleaned, and the Si substrate is etched using an HF solution to remove the SiO2 oxide layer on the surface of the silicon wafer. The cleaning time is set to 5 minutes; In the third step, the Si substrate is cleaned again using alcohol and high-purity water respectively.
[0061] Secondly, ALD technology is used on the obtained p-type Si substrate to alternately deposit a certain number of layers of Hf 0.5 Zr 0.5 O2 film and a certain number of Al2O3 films to obtain different doping concentrations [(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z Ferroelectric thin film, wherein x is the number of cycles of dopants, y is the total number of cycles of hafnium oxide and zirconium oxide, z is the number of repetitions of the xyx structural unit, and the ferroelectric thin film has a doping concentration of x / 2y. Specifically, in the first step, plasma enhanced atomic layer deposition technology was used to alternately grow one cycle of ZrO2 and one cycle of HfO2 on the substrate using [(CH3)2N]4Hf(TDMAH) as the Hf source, [(CH3)2N]4Zr(TDMAZ) as the Zr source, and oxygen plasma as the oxygen source. The alternating deposition of ZrO2 and HfO2 with a total of y cycles was repeated to obtain HfO2. 0.5 Zr 0.5 O2 film; In the second step, plasma enhanced atomic layer deposition technology was used to deposit (CH3)3Al(TMA) as the Al source and oxygen plasma as the oxygen source in the Hf 0.5 Zr 0.5 X layers of Al2O3 thin film are grown on the O2 thin film to complete the Hf 0.5 Zr 0.5 Al doping of O2 thin films; In the third step, plasma enhanced atomic layer deposition technology was used to alternately grow one cycle of ZrO2 and one cycle of HfO2 on the substrate using [(CH3)2N]4Hf(TDMAH) as the Hf source, [(CH3)2N]4Zr(TDMAZ) as the Zr source, and oxygen plasma as the oxygen source. The ZrO2 and HfO2 were alternately grown for a total of y cycles. 0.5 Zr 0.5 O2 film.
[0062] Step 4: Repeat the above process until a certain thickness of [(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z Ferroelectric film; wherein the doping structure is (yxy)×z (where x is the number of Al layer cycles, y is Hf 0.5 Zr 0.5 O2 is the number of cycles, z is the number of cycles of the overall structure).
[0063] Preferably, the doping basic units are 24-1-24, 18-1-18, 12-1-12 and 8-1-8.
[0064] Plating the obtained sample with a top electrode and a bottom electrode again; Specifically, the bottom electrode and the dot top electrode with a diameter of 600 μm were grown by using Pt material as the target material, the sputtering power was 30 W, the sputtering time was 3 min, and the thickness of the top electrode and the bottom electrode was 100 nm.
[0065] Finally, the obtained samples were annealed at high temperature.
[0066] Specifically, the obtained sample was subjected to high temperature annealing at 500-800° C. for 30 s at a heating rate of 50 K / s under an oxygen atmosphere and standard atmospheric pressure.
[0067] Embodiment 1: [(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z The doping structure of the ferroelectric film is (24-1-24)×2, and the sample is annealed at 600°C in an oxygen atmosphere.
[0068] Embodiment 2: [(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z The doping structure of the ferroelectric film is (24-1-24)×2, and the sample is annealed at 700°C in an oxygen atmosphere.
[0069] Embodiment 3: [(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z The doping structure of the ferroelectric film is (24-1-24)×2, and the sample is annealed at 800°C in an oxygen atmosphere.
[0070] Embodiment 4: [(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z The doping structure of the ferroelectric film is (8-1-8)×6, and the sample is annealed at 800°C in an oxygen atmosphere.
[0071] Embodiment 5: [(Hf 0.5 Zr 0.5O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z The doping structure of the ferroelectric film is (12-1-12)×4, and the sample is annealed at 700°C in an oxygen atmosphere.
[0072] Embodiment 6: [(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z The doping structure of the ferroelectric film is (12-2-12)×4, and the sample is annealed at 800°C in an oxygen atmosphere.
[0073] Comparative Example 1: Al x -(Hf 0.5 Zr 0.5 O2) y The doping structure of the ferroelectric film is uniformly doped with xy being 2-96, and the sample is annealed at 700° C. in an oxygen atmosphere.
[0074] Comparative Example 2: Al x -(Hf 0.5 Zr 0.5 O2) y The doping structure of the ferroelectric film is uniformly doped with xy being 2-96, and the sample is annealed at a temperature of 800° C. in an oxygen atmosphere.
[0075] Comparative Example 3: Undoped Hf 0.5 Zr 0.5 O2 ferroelectric thin film, the sample was annealed at 500℃ in an oxygen atmosphere.
[0076] Data analysis from Figure 2 The hysteresis loop of the Al-doped HZO ferroelectric film with a doping distribution of (24-1-24)×2 shows that the hafnium oxide-based ferroelectric film proposed in the present invention exhibits excellent ferroelectricity and has the highest remanent polarization at an annealing temperature of 700°C, with a 2Pr of 52.13 μC / cm 2 .
[0077] By comparison Figure 2 and Figure 3 , Figure 4It can be seen that the ferroelectric properties of the uniformly doped 2-96 Al-doped HZO film are similar to those of the undoped HZO film, and its 2Pr reaches 33.48μC / cm 2 It can be seen that the ferroelectricity of the HZO film cannot be effectively improved by direct doping, but after using the optimized structure doping adopted in this application, the ferroelectric performance of the Al-doped HZO film is significantly improved.
[0078] from Figure 5 It can be seen that after doping, the ferroelectric properties of the HZO film will not change significantly with the increase in the number of cycles. Therefore, the present application can effectively improve the wake-up effect of the HZO ferroelectric film, which is beneficial to the application of the film in storage devices.
[0079] from Figure 6 It can be seen that after doping, the leakage current of the HZO film is significantly reduced, but the unoptimized Al-doped HZO ferroelectric film is still easy to break down, even easier than the undoped film. After optimizing the doping distribution, the leakage current of the Al-doped HZO ferroelectric film is significantly reduced, and its breakdown characteristics are also improved to 7.4V. It can be seen that the doping structure provided in this application can effectively improve the insulation properties of the HZO film. from Figure 7 The comparison of the fatigue cycle characteristics of the sample with a doping structure of (24-1-24)×2 and an annealing temperature of 700℃ shows that the sample with the adjusted doping structure has a 8 After 100 cycles, it still showed a high residual polarization intensity, and its residual polarization intensity was still higher than that of the uniformly doped sample, showing higher durability. In addition, after fatigue, the leakage current of the sample regulated by the doping structure did not increase significantly, showing excellent anti-fatigue properties.
[0080] In summary, the present invention provides a doped hafnium oxide-based ferroelectric film based on doping distribution regulation, and its preparation method and application. By reasonably regulating the distribution of doping elements in the hafnium oxide film, the film is prompted to form more ferroelectric phases during the annealing process, thereby improving the ferroelectric properties of the hafnium oxide film; at the same time, the formation of film defects during the annealing process is suppressed to a certain extent, and the dielectric properties of the film are effectively improved. The technology provided by this application effectively improves the ferroelectric properties, dielectric properties and durability of the doped hafnium oxide-based ferroelectric film, deepens the understanding of the performance improvement of the hafnium oxide-based ferroelectric film, and promotes the development of the field of new practical ferroelectric films.
[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a doped hafnium oxide-based ferroelectric thin film based on doping distribution regulation, characterized in that: The following steps are involved: The unit structure of xyx is selected according to the doping concentration, and the ALD technology is repeatedly used on the substrate to obtain different doping concentrations [(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z A ferroelectric thin film, wherein x is the number of cycles of dopants in a unit structure, y is the total number of cycles of hafnium oxide and zirconium oxide in the unit structure, z is the number of repetitions of the unit structure, and the basic unit film has a doping concentration of y / 2x; =[(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z The ferroelectric film is plated with a top electrode and a bottom electrode, and then subjected to a high temperature annealing treatment to obtain a doped hafnium oxide-based ferroelectric film regulated based on doping distribution.
2. The method for preparing a doped hafnium oxide-based ferroelectric thin film based on doping distribution control according to claim 1, characterized in that: ALD technology is repeatedly used on the substrate to obtain different doping concentrations of [(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z Ferroelectric thin film Ferroelectric thin film specifically refers to: Plasma-enhanced atomic layer deposition technology is used to alternately deposit a set number of Hf layers on the substrate. 0.5 Zr 0.5 O2 film; Using plasma enhanced atomic layer deposition technology, Hf 0.5 Zr 0.5 A set number of Al2O3 films are deposited on the O2 film; Plasma enhanced atomic layer deposition technology was used to prepare Hf 0.5 Zr 0.5 O2 film deposition and Hf on substrate 0.5 Zr 0.5 O2 thin film with the same number of Hf 0.5 Zr 0.5 O2 film; Repeat the above steps several times until a [(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z Ferroelectric thin films.
3. The method for preparing a doped hafnium oxide-based ferroelectric thin film based on doping distribution control according to claim 2, characterized in that: Alternately deposit a set number of Hf layers on the substrate 0.5 Zr 0.5 The specific O2 film is: Using [(CH3)2N]4Hf(TDMAH) as Hf source, [(CH3)2N]4Zr(TDMAZ) as Zr source, and oxygen plasma as oxygen source, one cycle of ZrO2 and one cycle of HfO2 were alternately grown on a p-type Si substrate to obtain a set number of layers of Hf 0.5 Zr 0.5 O2 film.
4. The method for preparing a doped hafnium oxide-based ferroelectric thin film based on doping distribution control according to claim 3, characterized in that: Alternately cycle either ZrO2 1 to 12 times and HfO2 1 to 12 times, keeping the number of cycles of ZrO2 the same as the number of cycles of HfO2.
5. The method for preparing a doped hafnium oxide-based ferroelectric thin film based on doping distribution control according to claim 2, characterized in that: The dopant is any one of SiO2, Al2O3, La2O3, Gd2O3, and Y2O3.
6. The method for preparing a doped hafnium oxide-based ferroelectric thin film based on doping profile control according to claim 1, characterized in that: In Hf 0.5 Zr 0.5 The specific method of depositing a set number of Al2O3 films on an O2 film is: Plasma enhanced atomic layer deposition technology was used, with (CH3)3Al(TMA) as Al source and oxygen plasma as oxygen source. 0.5 Zr 0.5 A certain number of Al2O3 films are grown on the O2 film to complete the Hf 0.5 Zr 0.5 Al doping of O2 thin films; Using [(CH3)2N]4Hf(TDMAH) as Hf source, [(CH3)2N]4Zr(TDMAZ) as Zr source, and oxygen plasma as oxygen source, one cycle of ZrO2 and one cycle of HfO2 were alternately grown on Al2O3 film to obtain the same number of layers of Hf as in the substrate. 0.5 Zr 0.5 O2 thin film, obtain yxy (Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y Basic unit.
7. The method for preparing a hafnium oxide-based ferroelectric thin film by electrode-free annealing according to claim 1, characterized in that: For the obtained [(Hf 0.5 Zr 0.5 O2) y -Al x -(Hf 0.5 Zr 0.5 O2) y ] z The top electrode and bottom electrode of the ferroelectric thin film sample are specifically: Using the electrode material as the target, an ion sputtering coating process is used to grow a bottom electrode and a dot top electrode with a diameter of 50~700μm, and the electrode thickness is 20~120nm.
8. The method for preparing a doped hafnium oxide-based ferroelectric thin film based on doping profile control according to claim 1, characterized in that: High temperature annealing is specifically: The sample obtained from S2 was subjected to high temperature annealing at 600-800°C for 10-600s at a heating rate of 50°C / s under standard atmospheric pressure. The annealing atmosphere was any one of vacuum, nitrogen, and nitrogen-hydrogen mixed gas.
9. A hafnium oxide-doped ferroelectric thin film prepared by the method according to any one of claims 1 to 8 and regulated by doping profile.
10. Application of the doped hafnium oxide-based ferroelectric thin film based on doping distribution regulation according to claim 9 in random access memory, ferroelectric field effect transistor, ferroelectric memristor, and ferroelectric enhanced photodetector.
Citation Information
Patent Citations
Doping modification method of hafnium oxide-based ferroelectric film
CN118984646A
Cited By
Hafnium-based ferroelectric film and preparation method and application thereof
CN120916448A